2017
DOI: 10.1002/dev.21578
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol profiles differentiated in adolescents and young adult males with fragile X syndrome versus autism spectrum disorder

Abstract: Background Fragile X syndrome (FXS) and non‐syndromic autism spectrum disorder (ASD) are distinct disorders with overlapping behavioral features. Both disorders are also highly associated with anxiety with abnormal physiological regulation implied mechanistically. Some reports suggest atypical hypothalamus‐pituitary‐adrenal (HPA) axis function, indexed via aberrant cortisol reactivity, in both FXS and non‐syndromic ASD. However, no study has compared cortisol reactivity across these two disorders, or its relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 63 publications
(85 reference statements)
0
5
0
Order By: Relevance
“…Assessments took place as part of a larger study of social communication in the FMR1 premutation, which has been previously described (e.g., Klusek et al, 2017a ). Participants were recruited through their children who were participating in ongoing developmental studies of fragile X syndrome or ASD (e.g., Hogan et al, 2017 ; Matherly et al, 2018 ) or from the local community via social media, flyers, and word-of-mouth recruitment strategies targeting mothers of children with fragile X syndrome or ASD. Local recruitment methods included social media, word of mouth, and flyers posted at local pediatrician offices.…”
Section: Methodsmentioning
confidence: 99%
“…Assessments took place as part of a larger study of social communication in the FMR1 premutation, which has been previously described (e.g., Klusek et al, 2017a ). Participants were recruited through their children who were participating in ongoing developmental studies of fragile X syndrome or ASD (e.g., Hogan et al, 2017 ; Matherly et al, 2018 ) or from the local community via social media, flyers, and word-of-mouth recruitment strategies targeting mothers of children with fragile X syndrome or ASD. Local recruitment methods included social media, word of mouth, and flyers posted at local pediatrician offices.…”
Section: Methodsmentioning
confidence: 99%
“…Three additional males with FXS were recruited for the study but did not contribute data due to failure to complete >80% of the eye tracking trials (two males were unable to follow the instructions for calibration; one male refused to wear the head tracking sticker due to a sensory aversion). FXS data were collected as part of a longitudinal study focused on language development in males with FXS through adolescence and young adulthood (Abbeduto et al, 2019;Matherly et al, 2018), although previous publications from this study have not reported eye tracking data. Participants with FXS were recruited throughout the eastern and midwestern regions of the United States through social media, outreach to the National Fragile X Foundation Community Support Networks, and the Research Participant Registry Core of the Carolina Institute for Developmental Disabilities.…”
Section: Participantsmentioning
confidence: 99%
“…Likewise, a number of behaviors reflective of elevated stress, including crying and task avoidance, have not been associated with elevated cortisol (see Hardiman & Bratt, 2016 for review). However, elevated salivary cortisol has been linked to features of social anxiety, as indexed by gaze avoidance (Hall et al, 2009), physical avoidance (Roberts et al, 2009), and elevated parent ratings of social avoidance (Matherly et al, in press). Thus, physiological arousal may contribute to the presence and expression of social anxiety in FXS, but the bulk of evidence supports the hypothesis that it is more likely a systemic rather than a stimulus-bound reaction (e.g., a pervasive condition of hyperarousal versus elevated arousal in response to discrete conditions).…”
Section: Introductionmentioning
confidence: 99%